Transformations in Campus Placement Drives in Hospitality Institutions Across Madhya Pradesh : Post-COVID ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: Hospitality education plays a vital role in shaping students’ knowledge, skills and attitudes, transforming them into industry-ready professionals and enhancing their employability upon graduation. Campus placement drives are highly anticipated process for final-year hospitality students, as they provide opportunities to secure jobs immediately after completing their studies. However, the Covid-19 pandemic had a severe impact on the hospitality job market, leading to significant disruptions in placement opportunities. In the post-pandemic period, several studies have explored hospitality job prospects and the expectations of graduating students. Objectives: This study addresses an unexplored gap by focusing on three key objectives. First to examine the impact of the pandemic on placement opportunities for graduating batches from 2020 to 2023. Second to identify the essential attributes that prepare hospitality students for successful campus placements. Third to assess student satisfaction with placement drives and gathering recommendations for future improvements. Methodology: A descriptive research design was employed, utilizing a structured questionnaire completed by hospitality graduates from colleges across Madhya Pradesh between 2020 and 2023. A total of two hundred fifteen filled up questionnaires were received back of which two hundred and nine were usable. The data was analyzed using frequency and percentage represented in a tabular manner. Results: The findings reveal that most respondents perceived the pandemic as having a negative effect on job opportunities. As (73.68%) of the respondents felt that placement opportunities decreased. Additionally, the study highlights key attributes essential for successful placements, such as theoretical knowledge, strong communication and interpersonal skills. The dissatisfaction regarding the campus placement is on the decline from (54.84%) among 2020 graduates to (17.65%) among 2023 graduating batch. Conclusion: To enhance future campus placements, the study recommends initiatives such as career fairs, placement lectures, seminars and workshops at the institute level. Moreover, it emphasizes the need to expand the role of placement coordinators beyond organizing interviews to actively supporting students’ career development.
Keywords: Post-COVID; campus placement; hospitality education; graduates